2010
DOI: 10.1021/jp101508b
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Hydrogen Transfer between Cysteine Thiyl Radical and Glycine and Alanine in Model Peptides: Covalent H/D Exchange, Radical−Radical Reactions, and l- to d-Ala Conversion

Abstract: The reversible intramolecular hydrogen transfer reaction of peptide Cys thiyl radicals with Gly and Ala residues was studied in model peptides, where thiyl radicals were either generated through photochemical cleavage of disulfide bonds or through the reaction of Cys thiol with (*)CH(3) or CH(3)C(*)O radicals, or both, generated through photolysis of acetone. In D(2)O, the reversible hydrogen transfer leads to covalent H/D exchange, indicative of the location of intermediary carbon-centered radicals. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 52 publications
(92 reference statements)
2
48
0
Order By: Relevance
“…Strategy. Our strategy to identify D-amino acid containing sequences in photoirradiated mAb1 followed the methodology that we had applied to characterize C−H bonds sensitive to light-induced covalent H/D exchange, 3,[27][28][29]34,35 and which Huang et al 32 and Amano et al 33 had applied to detect pH-dependent epimerization in several IgG variants. In initial experiments, mAb1 was dissolved in D 2 O and lightinduced incorporation of deuterium into the peptide map of mAb1 monitored by HPLC−MS and HPLC−MS/MS analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Strategy. Our strategy to identify D-amino acid containing sequences in photoirradiated mAb1 followed the methodology that we had applied to characterize C−H bonds sensitive to light-induced covalent H/D exchange, 3,[27][28][29]34,35 and which Huang et al 32 and Amano et al 33 had applied to detect pH-dependent epimerization in several IgG variants. In initial experiments, mAb1 was dissolved in D 2 O and lightinduced incorporation of deuterium into the peptide map of mAb1 monitored by HPLC−MS and HPLC−MS/MS analysis.…”
Section: Resultsmentioning
confidence: 99%
“…This observation indicates hydrogen transfer from the first two amino acid residues to the thiyl radical. In fact, experimental and theoretical studies have shown that intramolecular hydrogen transfer to the thiyl radical is a facile process within polypeptides and cysteine ions [30][31][32][33]. [34] or CID of Nterminus amidated peptides [35].…”
Section: Formation Of C Z Ionsmentioning
confidence: 99%
“…However, these HAT reactions occurred not only with the α C-H bonds but also with the C-H bonds of the amino acid side chains[29]. Radiation chemistry, ESR, NMR and mass spectrometry experiments then provided evidence for intra molecular HAT reactions in model peptides[3032] as well as in glutathione (GSH)[3338], where HAT was observed between the Cys thiyl radical and the α C-H bonds of γ-Glu, Cys and Gly. More recently, pulse radiolysis experiments with Cys and several model compounds provided rate constants for intra molecular HAT reactions with the α C-H and the β C-H bond (Scheme 1, equilibria 2 and 1)[39].…”
Section: Introductionmentioning
confidence: 99%
“…While thiyl radicals were not generated through physiological processes in these studies, they are relevant to physiology as they demonstrate what can happen when thiyl radicals are generated on proteins. In the absence of oxygen, the reversible generation of carbon-centered radicals has led to the conversion of L-Ala to D-Ala in a model peptide[32], and to the sequence-specific generation of D-amino acids on IgG1[51]. Hence, thiyl radical generation on proteins is a viable source for D-amino acid generation, and such reactions have to be taken into account when simulating thiyl radical reaction pathways in proteins (see below).…”
Section: Introductionmentioning
confidence: 99%